Spatial Phenomenon of Multidimentional Poverty in Sumatera Island - Zulfa Emalia; Ida Budiarty (Budapest International Research and Critics University, 2022)
This research aims to analyze the conditions and developments, and factors affecting the provincial Multidimentional Poverty in Sumatera Island. The analysis methods that used in this research are spatial concepts and non-spatial concepts. The independent variable that used are Open Unemployment Rate, Per-capita Spending Rate, and The Level of Proper Sanitation. Results of this research suggest that Multidimentional Poverty shows a trend that decreases each year. Additionally, there is spatial autocorrelation of Multidimentional Poverty in the Province of Sumatera Island. Based on the estimation result, there is a positive significant effect of Open Unemployment Rate on Multidimentional Poverty without spatial concepts. And also, Per-capita Spending Rate as well as The Level of Proper Sanitation show a negative significant effect on Multidimentional Poverty without spatial concepts.